2009
DOI: 10.4049/jimmunol.182.1.466
|View full text |Cite
|
Sign up to set email alerts
|

CHAC1/MGC4504 Is a Novel Proapoptotic Component of the Unfolded Protein Response, Downstream of the ATF4-ATF3-CHOP Cascade

Abstract: To understand pathways mediating the inflammatory responses of human aortic endothelial cells to oxidized phospholipids, we previously used a combination of genetics and genomics to model a coexpression network encompassing >1000 genes. CHAC1 (cation transport regulator-like protein 1), a novel gene regulated by ox-PAPC (oxidized 1-palmitoyl-2-arachidonyl-sn-3-glycerophosphorylcholine), was identified in a co-regulated group of genes enriched for components of the ATF4 (activating transcription factor 4) arm o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
306
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(319 citation statements)
references
References 32 publications
12
306
1
Order By: Relevance
“…Atf4, Chop/Ddit3, Chac1, Trib3, and asparagine synthetase (Asns) are up-regulated during cellular responses to stress and were among the most highly induced genes by 25OHC ( Fig. 1C and supplemental Dataset S1) (13,34). Q-PCR assays in BMDMs confirmed that stress response genes were induced by 25OHC in a concentration-and time-dependent manner ( Fig.…”
Section: Ohc Suppresses Srebps Activates Lxrs and Induces Stressmentioning
confidence: 69%
“…Atf4, Chop/Ddit3, Chac1, Trib3, and asparagine synthetase (Asns) are up-regulated during cellular responses to stress and were among the most highly induced genes by 25OHC ( Fig. 1C and supplemental Dataset S1) (13,34). Q-PCR assays in BMDMs confirmed that stress response genes were induced by 25OHC in a concentration-and time-dependent manner ( Fig.…”
Section: Ohc Suppresses Srebps Activates Lxrs and Induces Stressmentioning
confidence: 69%
“…When the homology models of these proteins were superimposed on the g-GCT (C7orf24) structure they revealed very high structural similarity, despite no sequence similarity in their primary sequences (Fig 1A; supplementary Fig S2A online). Moreover, 39 YGSL 42 and E 116 residues of ChaC1, and 13 YGSL 16 and E 115 residues of YER163c are equivalent to the critical 22 YGSN 25 and E 98 residues of g-GCT that are involved in substrate binding and catalysis and superimposed very well on the corresponding residues of g-GCT (Fig 1B; supplementary Fig S2B online).…”
Section: Resultsmentioning
confidence: 87%
“…Glutathione depletion is an important factor for apoptosis initiation and execution. Moreover, ChaC1 has been shown as a proapototic factor in mammals [1,16]. To examine if the ChaC family proteins caused glutathione depletion in vivo and g-GACT, g-glutamylamine cyclotransferase; g-GCG, g-glutamylcyclotransferase-glutathione-specific; g-GCT, g-glutamyl cyclotransferase.…”
Section: Chac Overexpression Leads To Glutathione Depletionmentioning
confidence: 99%
“…This situation is likely to occur during the transition from a fasted state to that of satiation feeding where increased protein synthesis occurs through activation of the AKT/ mTOR pathway. Stimulation of the UPR leads to the activation of several transcription factors, resulting in the expression of DNAJ, HSPA1B, HSP90, and CHAC1 (52). There are three different UPR response pathways, regulated by PERK, ATF-6, and IRE-1.…”
Section: Protein Chaperones Are Activated In Response To Feedingmentioning
confidence: 99%